Effects of work-matched moderate- and high-intensity warm-up on power output during 2-min supramaximal cycling - Fujii, N.; Nishida, Y.; Ogawa, T.; Tanigawa, S.; Nishiyasu, Y. (Biology of Sport, 2018)
We tested the hypothesis that compared with a moderate-intensity warm-up, a work-matched high-intensity warm-up improves final-sprint power output during the last 30 s of a 120-s supramaximal exercise that mimics the final sprint during events such as the 800-m run, 1,500-m speed skate, or Keirin (cycling race). Nine active young males performed a 120-s supramaximal cycling exercise consisting of 90 s of constant-workload cycling at a workload that corresponds to 110% peak oxygen uptake (VO2peak) followed by 30 s of maximal cycling. This exercise was preceded by 1) no warm-up (control), 2) a 10-min cycling warm-up at a workload of 40% VO2peak (moderate-intensity), or 3) a 5-min cycling warm-up at a workload of 80% VO2peak (high-intensity). Total work was matched between the two warm-up conditions. Both warm-ups increased 5-s peak (observed within 10 s at the beginning of maximal cycling) and 30-s mean power output during the final 30-s maximal cycling compared to no warm-up. Moreover, the high-intensity warm-up provided a greater peak (577±169 vs. 541±175 W, P=0.01) but not mean (482±109 vs. 470±135W, P=1.00) power output than the moderate-intensity warm-up. Both VO2 during the 90-s constant workload cycling and the post-warm-up blood lactate concentration were higher following the high-intensity than moderate-intensity warm-up (all P=0.05). We show that work-matched moderate- (~40% VO2peak) and high- (~80% VO2peak) intensity warm-ups both improve final sprint (~30 s) performance during the late stage of a 120-s supramaximal exercise bout, and that a high-intensity warm-up provides greater improvement of short-duration (<10 s) maximal sprinting performance.